Pragmatic Analysis of Humor in American Animated Sitcom “American Dad! Season 17” - Dahlan, Dahlan (Journal of Islamic Culture and Literature (JICeL), 2023)
This research examines the floutingand breaking of maxims by thecharacters in the sitcom AmericanDad! Season 17 it employs the Gricecooperative principle theory as well asAttardo's function of humor. Thisresearch used qualitative researchmethod. The source of data isAmerican animated sitcom AmericanDad! Season17. The research revealstwo findings. The first is that all thefour types of flouting are employed bythe characters to create humor inAmerican Dad! season17. They areflouting maxim of quantity, floutingmaxim of quality, flouting maxim ofrelation, and flouting maxim ofmanner. Flouting maxim of relation ismostly employed by the characters tocreate humor, all the functions ofHumor are found in the sitcom; theyare social management,decommitment, mediation, anddefunctionalization. For breakingmaxim, only two functions are foundin the sitcom; they are socialmanagement, and defunctionalization.